Answer:
See below
Step-by-step explanation:
Let P(x) be a predicate over the variable x. Rules from logic tell us that the negation of ∀xP(x) is ∃x(¬P(x)). That is, the negation operator ¬ satisfies ¬(∀xP(x))≡∃x(¬P(x)). Similarly, ¬(∃xP(x))≡∀x(¬P(x)).
Apply these rules to each statement to obtain:
a) ∃ a fish x, x does not have gills.
b) ∃ a computer c, c does not have a CPU.
c) ∀ movie m, m is not over 6 hours long. ⇔ ∀ movie m, m is under 6 hours long.
d) ∀ band b, b has not won at least 10 Grammy awards. ⇔ ∀ band b, b has won less than 9 Grammy awards.